Digital Transformation Model of Tolerance Fiqh Education in The Context of Religious Plurality in University - Chanifah, Nur (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
Digital transformation in tolerance fiqh education is an urgent need amid the increasing phenomenon of religious intolerance and polarization in Indonesia, especially among students who live in a digital ecosystem full of biased and unverified religious information. This research aims to analyze the digital transformation model of tolerance fiqh education in higher education, as well as formulate a pedagogical approach that is relevant to the context of religious plurality and students' digital literacy needs. Using a qualitative research method with a literature study design, this study collects and analyzes primary and secondary sources in the form of classical and contemporary fiqh books, reputable international journals, national intolerance research reports, and studies on digital education. Data analysis was carried out through reduction techniques, thematic categorization, and hermeneutical interpretation to understand the conceptual relationship between digital transformation, religious moderation, and fiqh learning. The results of the study show that an effective model of tolerance fiqh education must be hybrid, combining face-to-face for book studies and legal discussions, as well as digital platforms for simulation of intolerance cases, virtual interreligious dialogue, and access to global literature. These findings confirm that the critical and ethical integration of technology can strengthen students' competence of tolerance, interfaith empathy, and religious digital literacy.